A functional study of the inner features of CAPS hand drawn faces: contributes to its construct validity - Grácio, Joana Catarina Gonçalves (2014)
The Children's Anxiety and Pain Scales - CAPS (Kuttner & LePage, 1989) is the only faces measure to date aimed at separately assessing anxiety and pain intensity through self-report. Despite early indications that the two sets of faces retained in the CAPS possess some face validity regarding the constructs of anxiety/fear and pain, the degree to which they afford a means of differentiating them has remained questionable, especially in younger children. In this study, the inner features of faces in each set were taken as factors in integration tasks performed by children differing in age (6-8 and 9-11 years old) and pain experience (pain-free and acute postoperative pain). Differences in the integration patterns were observed across the two sets, along with distinct profiles of relative importance among upper- and lower-face features. These differences did not depend on the assigned judgment dimension (intensity of conveyed pain or of conveyed fear), and partly concurred with collateral evidence on the relative importance of facial features in prototypical pain and fear expressions. Overall, outcomes were supportive of several facets of the construct validity of the CAPS.